2019
DOI: 10.1016/j.ijpx.2019.100014
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of Alendronate depot microspheres based on novel poly(-ε-caprolactone)/Vitamin E TPGS copolymers

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
4
9
0
1
Order By: Relevance
“…PCL spectrum showed characteristic bands that are in accordance with the literature 34–38 . ALD spectrum provided the following characteristic bands: hydroxyl group bending vibration around 916 cm −1 , amino group stretching vibration around 3478 cm −1 and P = O stretching vibration around 1016 and 1042 cm −1 , which is in agreement with the bands reported in the literature 39–42 …”
Section: Resultssupporting
confidence: 89%
“…PCL spectrum showed characteristic bands that are in accordance with the literature 34–38 . ALD spectrum provided the following characteristic bands: hydroxyl group bending vibration around 916 cm −1 , amino group stretching vibration around 3478 cm −1 and P = O stretching vibration around 1016 and 1042 cm −1 , which is in agreement with the bands reported in the literature 39–42 …”
Section: Resultssupporting
confidence: 89%
“…Moreover, Shin et al also reported similar shifts in the abovementioned bands when the FTIR spectrum of methoxy PEG was compared to the spectra of methoxy PEO 5000 - b -PCL with different molecular weights of PCL (Mn ~ 4000–17,000 Da) [ 38 ]. These observations verify the presence of intermolecular interactions occurring during the polymer synthesis [ 36 , 39 ].…”
Section: Resultssupporting
confidence: 82%
“…As depicted in the thermograms ( Figure 6 ), ATRA showed a slight endothermic peak at about 146 °C and a relevant peak associated to melting at about 183 °C [ 49 ]. TPGS alone gave an endothermic sharp peak of melting at around 43 °C and a broad peak at 32 °C, due to the minor presence of an amorphous solid [ 50 ]. The DSC thermograms of ATRA-loaded micelles showed only the melting peak of TPGS.…”
Section: Resultsmentioning
confidence: 99%